Developing cultural competence in general practitioners: an integrative review of the literature - Watt, Kelly (BMC Fam Pract, 2016)
BACKGROUND: Cultural competence is a broad concept with multiple theoretical underpinnings and conflicting opinions on how it should be materialized. While it is recognized that cultural competence should be an integral part of General Practice, literature in the context of General Practice is limited. The aim of this article is to provide a comprehensive summary of the current literature with respect to the following: the elements of cultural competency that need to be fostered and developed in GPs and GP registrars; how is cultural competence being developed in General Practice currently; and who facilitates the development of cultural competence in General Practice. METHODS: We conducted an integrative review comprising a systematic literature search followed by a synthesis of the results using a narrative synthesis technique. RESULTS: Fifty articles were included in the final analysis. Cultural competence was conceptualized as requiring elements of knowledge, awareness/attitudes and skills/behaviours by most articles. The ways in which elements of cultural competence were developed in General Practice appeared to be highly varied and rigorous evaluation was generally lacking, particularly with respect to improvement in patient outcomes. Formal cultural competence training in General Practice appeared to be underdeveloped despite GP registrars generally desiring more training. The development of most aspects of cultural competence relied on informal learning and in-practice exposure but this required proper guidance and facilitation by supervisors and educators. Levels of critical and cultural self-reflection amongst General Practitioners and GP registrars varied and were potentially underdeveloped. Most standalone training workshops were led by trained medical educators however the value of cultural mentors was recognised by patients, educators and GP registrars across many studies. CONCLUSIONS: Cultural competency development of GP registrars should receive more focus, particularly training in non-conscious bias, anti-racism training and critical self-reflectiveness. There is a need for further exploration of how cultural competence training is delivered within the GP training model, including clarifying the supervisor’s role. It is hoped this discussion will inform future research and training practices in order to achieve quality and respectful care to patients across cultures, and to remove health inequities that exist between cultural groups.